2017
DOI: 10.1159/000478070
|View full text |Cite
|
Sign up to set email alerts
|

Activation of COX-2/mPGES-1/PGE2 Cascade via NLRP3 Inflammasome Contributes to Albumin-Induced Proximal Tubule Cell Injury

Abstract: Background/Aims: The activation of NOD-like receptor family, pyrin domain containing3 (NLRP3) inflammasome has been shown to be positively correlated with the severity of proteinuria in chronic kidney disease (CKD) patients. Prostaglandin E2 (PGE2), an important inflammatory mediator, is also involved in various kidney injuries. The aim of the present study was to investigate the involvement of NLRP3 inflammasome and PGE2 synthetic pathway in albumin-induced renal tubular injury. Methods: Murine proximal tubul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 39 publications
2
13
0
Order By: Relevance
“…Although not statistically significant in our study, we observed a lower proportion of patients with elevated NLRP3 (p = 0.11) among ibuprofen users, an NSAID well associated with a reduced risk of PD 10 . These data are consistent with previous reports suggesting certain NSAIDs are capable of inhibiting NLRP3 95 and studies reporting mechanistic links between one major NSAID target, COX2, and the NLRP3 inflammasome 96,97 . Based on the frequent reporting of "overthe-counter" anti-inflammatory drug use by PD patients, our data indicating elevated NLRP3 in PD is likely an underrepresentation of the actual relationship between circulating pyroptosis-related proteins and PD.…”
Section: Discussionsupporting
confidence: 93%
“…Although not statistically significant in our study, we observed a lower proportion of patients with elevated NLRP3 (p = 0.11) among ibuprofen users, an NSAID well associated with a reduced risk of PD 10 . These data are consistent with previous reports suggesting certain NSAIDs are capable of inhibiting NLRP3 95 and studies reporting mechanistic links between one major NSAID target, COX2, and the NLRP3 inflammasome 96,97 . Based on the frequent reporting of "overthe-counter" anti-inflammatory drug use by PD patients, our data indicating elevated NLRP3 in PD is likely an underrepresentation of the actual relationship between circulating pyroptosis-related proteins and PD.…”
Section: Discussionsupporting
confidence: 93%
“…Proximal tubules exposed to albumin also augmented production of profibrotic TGF-β and its type II receptor as well as accumulation of ECM components collagen IV, laminin, and fibronectin in vitro[127129]. More recent data has linked protein reabsorption and lysosomal rupture with stimulation of the NOD-like receptor family, pyrin domain containing 3 (NLRP3) inflammasome in the proximal tubule[130, 131]. Albumin exposure to the proximal tubule also impairs autophagy in vitro by activating mammalian target of rapamycin (mTOR), a known autophagy inhibitor.…”
Section: Introductionmentioning
confidence: 99%
“…It has also been reported that NF-κB induces the activation of COX-2 genes in primary dysmenorrhea [44], and some studies have shown that the NLRP3 inflammasome upregulates NF-κB activation and promotes COX-2 expression [45]. Moreover, it has been reported that NLRP3 inflammasomes could be responsible for mediating the albumin effect on activating the COX-2/mPGES-1/PGE2 cascade, but the role of NF-kB in this case is not known [12]. The effect of NLRP3 on COX-2 is not clear, but we think that NLRP3 regulates COX-2 through the NF-κB pathway, and the NLRP3 inflammasome might be involved in the pathological progression of PD through the NF-κB/COX-2/PG pathway.…”
Section: Discussionmentioning
confidence: 99%
“…The assembly of the NLRP3 inflammasome as stimulated by NLRP3 irritants triggers proteolytic cleavage of dormant procaspase-1 into active caspase-1, which converts the cytokines pro-IL-1β and pro-IL-18 into mature and biologically active IL-1β and IL-18, respectively, leading to a cascade of deleterious inflammation [10]. Moreover, there is increasing evidence indicating that the NLRP3 inflammasome plays a regulatory role in the expression of COX-2 via the NF-κB pathway [11,12]. Our previous studies have found that the NLRP3 inflammasome can be activated and expressed in PD, and effective traditional electroacupuncture therapy to treat PD is associated with the inhibition of NLRP3 inflammasome activation [13].…”
Section: Introductionmentioning
confidence: 99%